On Marc Thury’s Les Tables Tournantes - Alvarado, Carlos S. (Journal of Scientific Exploration, 2016)
This is a brief comment about Marc Thury's book Les Tables Tournantes (1855). A few aspects of the books are summarized. This includes tests the authored conducted, and some theoretical concepts presented to explain the movement of tables.